1976
DOI: 10.1210/jcem-43-3-533
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thyrotropin, Thyroxine, and Triiodothyronine Relationships in Man

Abstract: The physiologic relationships of plasma TSH, T4 and T3 levels measured every 20 min in seven healthy young men and one healthy young woman have been investigated. A nocturnal TSH surge was observed in all subjects on both nights of the 36-48 h baseline observation period. In males the maximum plasma TSH value occurred at 2300 h. The mean peak TSH level was 2.0 +/- 0.3 (se) muU/ml compared with a mean of 1.3 +/- 0.9 muU/ml for the entire baseline records of the 8 subjects. The effect of iv infusion of 32-1000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
3
4

Year Published

1978
1978
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(40 citation statements)
references
References 15 publications
3
30
3
4
Order By: Relevance
“…The lack of diurnal variation in plasma T4and T3levels agrees with the results of previous reports (Azukizawa et al, 1976;O'Connor et al, 1974). Our results by the6hr interval sampling for2days do not suggest the possibility of diurnal variation of plasma reverse T3concentration.…”
Section: Radioimmunoassayssupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of diurnal variation in plasma T4and T3levels agrees with the results of previous reports (Azukizawa et al, 1976;O'Connor et al, 1974). Our results by the6hr interval sampling for2days do not suggest the possibility of diurnal variation of plasma reverse T3concentration.…”
Section: Radioimmunoassayssupporting
confidence: 92%
“…Computational analysis of the data failed to reveal any correlations between the diurnal rhythm of plasma TSH levels and the fluctuations of thyroxine (T4) or3, 5, 3'-triiodothyronine (T3) in plasma (Azukizawa et al, 1976). It has been suggested that the circadian rhythm of TSH secretion is the result of the inhibitory action of plasma cortisol because there is an inverse relationship between their circadian patterns (Nicoloff et al, 1970), and because of the suppressive effect of dexamethasone on TSH secretion (Wilber and Utiger, 1969).…”
Section: Synopsismentioning
confidence: 99%
“…We found that there was no correlation between the total thyroid hormone levels and TSH levels in samples taken at 20-min intervals (Azukizawa et al, 1976). Recently Weeke and Gundersen observed that the diurnal rhythm of serum free triiodothyronine and serum TSH levels were synchronous with low levels in the daytime and high levels at night (Weeke and Gundersen, 1978).…”
mentioning
confidence: 50%
“…Since the development of a highly sensitive radioimmunoassay for hTSH has made it possible to measure the basal level of serum TSH, a diurnal variation in serum TSH has been demonstrated in normal subjects (Nicoloff et al, 1970 ;Patel et al, 1972 ;Weeke, 1973 ;Azukizawa et al, 1976). However, the role and mechanism of the diurnal change in the serum TSH concentration are still unknown.…”
mentioning
confidence: 99%
“…After the baseline blood samples were obtained, 7hypothyroid patients were orally given300mg of r-oryzanol (Ohtsuka Pharmaceutical Co., Japan) and blood samples were subsequently drawn at1, 2, 4and6hr. Three days later, blood was taken from these patients at Diurnal TSH variations in man was recently shown by some investigators (Weeke and Laurberg, 1976;Azukizawa et al, 1976;Weeke and Gundersen, 1978) employing single antibody wick-chromatographic radioimmunoassays (Weeke and rskow1973) or high-sensitivity radioimmunoassay technique for TSH (Pekary et al, 1975 ic action of r-oryzanol (Itaya et al, 1976).…”
Section: Methodsmentioning
confidence: 93%